2021
DOI: 10.1038/s41467-021-25982-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ChAdOx1 nCoV-19 (AZD1222) vaccine against SARS-CoV-2 lineages circulating in Brazil

Abstract: Several COVID-19 vaccines have shown good efficacy in clinical trials, but there remains uncertainty about the efficacy of vaccines against different variants. Here, we investigate the efficacy of ChAdOx1 nCoV-19 (AZD1222) against symptomatic COVID-19 in a post-hoc exploratory analysis of a Phase 3 randomised trial in Brazil (trial registration ISRCTN89951424). Nose and throat swabs were tested by PCR in symptomatic participants. Sequencing and genotyping of swabs were performed to determine the lineages of SA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The study also pointed to the maintained protection of ChAdOx1 against the Gamma variant despite a dip in efficacy compared to other variants. However, the conclusion was unpowered due to the limited cases and wide confidence interval [ 179 ]. On ChAdOx1 effectiveness against Delta variant, Bernal et al [ 145 ] estimated one dose effectiveness against the symptomatic disease of 30.7% (95CI: 25.2–35.7) and 67% (95CI: 61.3–71.8) for two doses.…”
Section: Current Vaccine Efficacymentioning
confidence: 99%
“…The study also pointed to the maintained protection of ChAdOx1 against the Gamma variant despite a dip in efficacy compared to other variants. However, the conclusion was unpowered due to the limited cases and wide confidence interval [ 179 ]. On ChAdOx1 effectiveness against Delta variant, Bernal et al [ 145 ] estimated one dose effectiveness against the symptomatic disease of 30.7% (95CI: 25.2–35.7) and 67% (95CI: 61.3–71.8) for two doses.…”
Section: Current Vaccine Efficacymentioning
confidence: 99%
“…Approximately 14 days after the second dose, the AZD-1222 vaccine showed 66.7% efficacy against the SARS-CoV-2 prototype stain ( 71 ), 70.4% against Alpha ( 72 ), 10.4% against Beta ( 73 ), 66% against Delta ( 42 ). Although the number of cases to analyze was limited, ChAdOx1 nCoV-19 showed 64% efficacy against Gamma variant infection ( 74 ). These results indicated that the vaccine lost its protective effect against the Beta variant, but still was effective against other VOC.…”
Section: Efficacy Of Covid-19 Vaccines Against Sars-cov-2 Variantsmentioning
confidence: 99%
“…Although the Pfizer-BioNTech COVID-19 vaccine provoked an immune response that attenuated the severity of the disease among those elderly patients from severe symptoms in non-vaccinated patients to mild symptoms in this vaccinated patient, there was a reduction of the vaccine efficacy against this Brazilian variant [245]. In a study that included 9433 participants who had two doses of ChAdOx1 nCoV-19/AZD1222 vaccine (University of Oxford, AstraZeneca, and the Serum Institute of India), the efficacy of the vaccine on the B.1.1.28 lineage was 73%, and this vaccine had 95% protection rate from COVID-19 hospitalization [246].…”
Section: B1351 Lineage (Beta or Gh501yv20)mentioning
confidence: 99%